Effect of natural blue-green algal cells lysis on freshwater quality - Kilulya, Kessy; Msagati, Titus; Mamba , Bhekie (Tanzania Journal of Science, 2017)
Blue-green algae grow in freshwater bodies when they are provided with suitable factors such as nutrients and appropriate weather conditions. Their cell lysis occurs naturally when they encounter unfavourable conditions. This study reports on the types and amounts of fatty acids added into freshwater due to the algal cell lysis. The investigation on the amount of fatty acids released into water due to algal cells lysis was performed by placing samples in two compartments, one with no light allowing the algae cells to die while the other compartment was kept in favourable conditions enough to sustain the life of algae. Fatty acids were then extracted from both dead and living cells as well as their respective water filtrates. Determination of fatty acids was performed using GCxGC-TOF-MS. Identified fatty acids were mainly; tetradecanoic acid, 7-hexadecenoic acid, hexadecanoic acid, 9,12,15-octadecatrienoic acid, 6,9,12,15-octadecatetraenoic acid, 9,12-octadecadienoic, 9-octadecenoic and octadecanoic acids. It was found that water from the dead cells had higher amounts of fatty acids than water samples from the living cells. Unsaturated fatty acids increased from 0.85 mg/L to 2.70 mg/L in filtrate water from the dead algae. The pH of water samples from the dead cells decreased from 6.8 to 6.1. Keywords; Algae, cells lysis, Fatty acids, gas chromatography time-of-flight mass spectrometry, water quality